Recent Advances in Non-Viral Vectors for Gene Therapy and Gene Delivery: From Lipid Nanoparticles to Engineered Extracellular Vesicles - Yongfeng Yang; Tingting Song; Kaili Huang; Hong Huang; Maoyuan Zhao; Yi Li (Pharmaceutics, 2026)
Gene therapy and genome editing increasingly depend on the safe, effective, and cell-selective delivery of nucleic acids and protein–nucleic acid complexes. Although viral vectors remain important for applications requiring durable gene expression, non-viral vectors offer advantages in cargo capacity, modularity, transient expression, potential repeat dosing, and avoidance of vector–genome integration. Lipid nanoparticles (LNPs), polymeric nanoparticles, inorganic nanomaterials, extracellular vesicles (EVs), and biomimetic hybrid systems have consequently become central platforms for delivery of siRNA, mRNA, plasmid DNA, antisense oligonucleotides, and CRISPR-based genome editors. Among these, ionizable LNPs are currently the most clinically mature non-viral technology, supported by the clinical success of siRNA therapeutics and mRNA vaccines, as well as the emergence of in vivo CRISPR therapies. Nevertheless, efficient endosomal escape, cell-type-selective targeting, extrahepatic delivery, and repeat-dose tolerability remain substantial barriers. Polymeric vectors provide broad chemical tunability, allowing adjustment of charge density, degradability, stimulus responsiveness, intracellular trafficking, and cargo release. However, toxicity and batch-to-batch reproducibility remain key concerns. EVs provide a biologically derived alternative with favorable membrane interfaces and potential advantages for protein and ribonucleoprotein delivery, but their clinical translation is constrained by heterogeneity, loading efficiency, product characterization, and scalable manufacturing. This review summarizes recent advances in non-viral gene-delivery platforms, compares their strengths and limitations, and discusses future directions in cell-selective delivery, endosomal escape, transient delivery of genome-editing machinery, engineered EVs, hybrid vectors, and manufacturing-oriented development. The field is transitioning from organ-level delivery toward delivery of the correct payload to the correct cell type at a clinically relevant exposure and safety margin.